Beyond Interaction: The relational construct of 'Transactional Presence' - Shin, Namin (Open Learning: The Journal of Open, Distance and e-Learning, 2002)
This paper presents the novel construct of 'Transactional Presence' in consideration of a distance student's perceptions of psychological presence on the part of teachers, peers, and institutions. Relevant distance education literature is analyzed through the lens of interpersonal relationships, and concepts such as telepresence and social presence are drawn from media and communication studies. When the two streams of literature reviewed are merged, it is conjectured that the perception of presence concerned must be influenced by distance students' idiosyncratic needs for connection with learning resources and sources of support. This notion of presence, designated 'Transactional Presence', is defined as the degree to which a distance student perceives the availability of, and connectedness with, other parties involved in a given distance education setting. The construct's potential significance is explored in view of enriching distance education theory and research.